An Online Family Literacy and Wellness Program for Latino Dual Language Learners: Pilot Randomized Waitlist Controlled Trial - Kevin D Guerrero; Lucia Lakata; Daniel Lima; Caroline Mendoza; Nila Uthirasamy; Lesley M Morrow; Silvia Perez-Cortes; Maria Pellerano; Alicja Bator; Pamela Ohman Strickland; Benjamin F Crabtree; Manuel E Jimenez (JMIR Pediatrics and Parenting, 2025)
Abstract BackgroundEarly childhood interventions can simultaneously promote positive health and early language experiences, but implementation and health equity often receive insufficient attention during the development process. ObjectiveWe apply a health equity lens to refine and pilot-test a family literacy and wellness program designed for Latino dual language learners (DLLs) entering kindergarten and their caregivers. MethodsIn collaboration with a parent and community advisory board, we refined an 8-week family literacy and wellness program and conducted a pilot randomized controlled trial (RCT) with a waitlist control. The program, specifically designed by our interprofessional team for Latino DLLs, uses health topics (ie, nutrition, physical activity, sleep, and social-emotional development) to (1) introduce foundational language and literacy skills to children; (2) empower families to engage in health and home literacy activities using a strengths-based approach; and (3) encourage maintenance of families’ home language. We assessed reach by collecting sociodemographic information; attendance and acceptability using a parent survey; and preliminary effects on home literacy activities through a validated parent-report instrument (StimQ2 ResultsParents and community advisors informed the program content. A total of 32 parent-child dyads were enrolled in the pilot RCT. All parents identified as Latino, and half had not completed high school, indicating that we reached the intended audience. Parents rated the program as highly acceptable, and 23 (72%) participants attended at least half of the sessions. After participation, group 1 had higher StimQ2PP ConclusionsSimilar interprofessional collaborations may be a promising strategy to promote equity in early language experiences for Latino DLLs and their families.